The Influence of Job Training, Career Development, and Working Conditions on Employee Performance at PT. Hilon Sumatera - Lubis, Irsad; Sijabat, Lastri Putri BR (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to determine the effect of job training, career development and working conditions on employee performance at PT Hilon Sumatra. The population of this study was 53 people and the number of samples through a census was 53 people. The analysis technique used in this study is multiple linear regression. The results of this study indicate that the job training variable has a positive and significant effect on employee performance at PT Hilon Sumatra. with a regression coefficient value of 1.199 and a significance value of 0.000 <0.05 (smaller than the error tolerance value). Career development has a positive but insignificant effect on employee performance at PT Hilon Sumatra with a regression coefficient value of 0.077 and a significance value of 0.238 ÿ 0.05 (greater than the error tolerance value). Working conditions have a positive and significant effect on employee performance at PT Hilon Sumatra with a regression coefficient value of 0.170 and a significance value of 0.007 <0.05 (smaller than the error tolerance value).